Teachers’ Teaching Strategies in ESP: A Descriptive Study at Malahayati University - Rahmawati, Hamida Nur; Mar’an, Desy Awal (CV. Tripe Konsultan, 2024)
This study explores teaching strategies employed by English for Specific Purposes (ESP) teachers at a private university in Lampung, focusing on two faculties: Medical and Economics. Using a qualitative research design, six English teachers were interviewed to examine their practices in delivering ESP instruction. The study aimed to understand how teaching strategies are tailored to address the differing academic backgrounds and English proficiency levels of medical and economics students. Data were analyzed using the framework outlined by Miles et al. (2018), focusing on themes such as teaching materials, subject matter, classroom activities, and the use of students’ native language. Findings reveal that medical English instruction often integrates specialized content, such as medical terminology, authentic texts, and professional communication tasks, with teachers systematically introducing technical vocabulary and employing task-based learning. Conversely, economics instruction emphasizes real-world scenarios through case studies, simulations, and group discussions, but teachers face challenges in adapting resources due to the lack of standardized materials. Both groups of students displayed distinct learning characteristics, requiring teachers to adopt flexible approaches, such as code-switching to ensure comprehension and incorporating digital tools like Quizizz and Kahoot to enhance engagement. The study highlights the critical role of contextualized and adaptable teaching strategies in ESP, emphasizing the need for specialized materials, professional development for teachers, and greater collaboration between language educators and subject-matter experts. These findings provide valuable insights for improving ESP instruction to meet the diverse needs of learners in higher education.